The circular economy and the sustainability of materials in the fashion industry - Costa, Junior de Jesus (2022)
Materials are the basis of any product and necessary in any production chain. Industry uses the same inputs from the industrial revolution, beginning of the problem over scalability and disposal promoted by the linear economy. The fashion industry is considered one of the most pollutants, in addition to production methods, has evolved little into account the raw materials, based on the manufacture of products in oil and cotton polymeric derivatives. Due to the high demand of the entire textile chain, cotton proved not sustainable and caused negative impacts on the environment. Plastic materials from oil took over all markets, their industrial efficiency compared to environmental impact demonstrates the destructive potential of this polymer for biodiversity. Its degradation is slow and takes about 400 years, leaving a trail of destruction that includes microplastics, already discovered in food and bloodstream. Industry needs new raw materials that reduce the consumption of non-renewable resources and expand alternatives to cotton and polyester. Thus, the research of the current panorama and the sustainability of the fashion industry in relation to materials is defined for this study. The research results point to the need for changes in the production process, industry investments in alternatives and an important reduction in society consumption.